Using the water quality index (WQI), and the synthetic pollution index (SPI) to evaluate the groundwater quality for drinking purpose in Hailun, China - Tian, Hui; Du, Jizhong; Sun, Qifa; Liu, Qiang; Kang, Zhuang; Jin, Hongtao (Penerbit Universiti Kebangsaan Malaysia, 2020)
Due to the impact of human agricultural production, climate and environmental changes. The applicability of groundwater for drinking purposes has attracted widespread attention. In order to quantify the hydrochemical characteristics of groundwater in Hailun and evaluate its suitability for assessing water for drinking purposes, 77 shallow groundwater samples and 57 deep groundwater samples were collected and analyzed. The results show that deep groundwater in aquifers in the study area is weakly alkaline, while that in shallow is acidic. The abundance is in the order HCO3 - > Cl- > SO4 2- for anions, and Ca2+> Na+> Mg2+ for cations. Groundwater chemical type were dominated by HCO3 -Ca, HCO3 -Ca• Mg, and HCO3 -Ca• Na. Correlation analysis (CA) and Durov diagram showed that rock weathering and dissolution, human activities, and the hydraulic connection between shallow and deep water are the main reasons affecting the chemical composition of water in Helen. The analysis of water samples based on the WQI model showed that about 23.37, 23.37, 32.46, 12.98, and 7.79% of the shallow groundwater samples were excellent, good, poor, very poor, and unsuitable for drinking purposes, respectively, and that 61.40, 30.90, 5.26, 1.75, and 1.75% of the deep groundwater samples were excellent, good, poor, very poor, and unsuitable for drinking purposes, respectively. The analysis of groundwater samples based on the SPI model showed that 92.98% of the deep groundwater samples were suitable grade, while that 40.25% of the shallow groundwater samples were suitable grade. The spatial distribution maps of the WQI and SPI show that most of the deep groundwater resources in the study area are clean and suitable for drinking, despite the risks of the shallow groundwater in the north and southwest of the study area.